Statistical Analysis of Temporal Oscillations of Total Ozone Rate in Esfahan Atmosphere (نشریه جغرافیا و برنامه‌ریزی, 2012)
Ozone is a very small part of earth atmosphere, but its presence is nevertheless vital to human well-being. Most ozone resides in the upper part of the atmosphere. This region called the stratosphere is more than 10 kilometers above earth's surface. About 90 percent atmospheric ozone is contained in the ozone layer or ozonosphere which shields every living thing from ultraviolet light from the sun. Total ozone is all the ozone in the atmosphere. Total ozone values often report in Dobson units. Typical values vary between 200 to 500 Dobson over the globe. Total ozone varies strongly with spatial (latitude) and temporal over the planet. This paper with using different statistical as regression analysis, variance analysis and Student-Newman-Keuls (SNK) methods tried to discover the relationship between total ozone and time variation in monthly, seasonal and annual time scale in Isfahan ozone metric station. Analysis of variance shows significant different between time series means p<0.01. The best series agreement with the among of ozone is seasonal series so that  average of among of ozone shows a significant in each season with S.N.K test but monthly and yearly  mean of ozone don't show significant difference in all of months and years . Spring has the maximum of seasonal mean of ozone and fall has the minimum of it. Results of study on trend indicate a no significant trend in the annual mean in the time series.